Góry Mariana Pankowskiego – przestrzeń emigracji i „emigracji”? - Dutka, Elżbieta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The interpretation of the forgotten volume of „Wiersze alpejskie” (Alpine Poems) by Marian Pankowski, published in Brussels in 1947 is, in the presented article, a starting point for reflection on the various dimensions and meanings of emigration in the biography and work of the artist. Paying attention to the topographic details allows to read the collection of poems not only as a poetic record of sensations related to the mountain trek, but also as a testimony to the writer’s dilemmas and his artistic explorations. However, the comparison with the later work „Z Auszwicu do Belsen” (From Auszwic to Belsen) reveals the genesis of „Wiersze alpejskie” (Alpine Poems) as related to the first post-war holiday trip of the poet and directs our attention to his traumatic experiences, absent, displaced in the lyrics, which can be read as the area of another emigration i.e. escape from painful memories.
Marian Pankowski’s Mountains – Space of Emigration and “Emigration”?
Keywords: Marian Pankowski; The Alps; emigration; memory; Auschwitz; Alpy; emigracja; pamięć